Islamic and conventional banks: an empirical study of liquidity risk - Saidi, Normaizatul Akma; Md Nassir, Annuar; Yahya, Mohamed Hisham; Abdullah, Amalina (Global Business and Social Entrepreneurship Resources, 2017)
The banking system consists of conventional banks and Islamic banks. These two type of banks are both exposes to risk. The financial crisis is rooted from the liquidity risk. Therefore, this study is keen to examine the liquidity risk for Islamic and conventional banks in Southeast Asia for a period of 2010 to 2014. The liquidity ratios are used as the measurement of liquidity risk. Then, the descriptive statistic is used to compare the liquidity risk between Islamic and conventional banks. Based on the result of banks in all countries, the study found that the Islamic banks are exposes to a higher liquidity risk (based on mean value of NLDSF) as compared to the conventional banks.